THE INFLUENCE OF PEER GROUP SUPPORT ON STUNTING PREVENTION BEHAVIOR IN MOTHERS OF CHILDREN UNDER FIVE YEARS OF AGE 0-5 YEARS OLD - Agustin, Widat; Fatmawati, Lilis; Tiara Revita , Natalia Christin (jfpublisher, 2025)
Introduction. Stunting or shortness of stature is a condition of not achieving one of the health indicators characterized by a child's lower height (TB) when compared to other children of the same age. Stunting can cause adverse effects on a person's survival. The purpose of this study is the effect of peer group support on the prevention of stunting in mothers who have children under five years of age 0-5 years. Methode. This research is a Quantitative research with a cross sectional design conducted in the working area of the Sangkapura Health Center, Suwari Village, Gresik Regency. The population of this study amounted to 64 people with a sample size of 55 mothers. Sampling technique with porpusive sampling technique, analyzed univariate and bivariate using wilcoxcon test. Result & Analysis. The results of the research analysis showed that out of 55 mothers, most (85.5%) had good knowledge about stunting prevention, most mothers (90.0%) had a positive attitude, most mothers (89.1%) had positive behavior. A value of (p=0.000) was obtained (α <0.05). Discussion. Based on these results, the hypothesis H1 is accepted and H0 is rejected, which shows that there is an effect of knowledge, attitudes and behavior of Peer Group Support on Stunting Prevention in mothers who have children under five years of age 0-5 years.